Analisis Kepatuhan Wajib Pajak Usaha Mikro Kecil dan Menengah (UMKM) : (Studi Kasus pada Desa Habi) - Maria Lifani Dua Lelu; Henrikus Herdi; Wihelmina Maryetha Y. Jaeng (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Analysis of MSME taxpayer compliance in Habi Village. The purpose of this research was to determine and analyze the compliance of MSME taxpayer in Habi Village in paying taxes. This research employed a descriptive qualitative study, and the data collection teachnque for writing this thesis used the interview method. The number of informants in this study were five MSMEs in Habi Village. The research revealed thas two MSME owner in Habi Village had registered their businesses as taxpayers, while there others had not obtained an NPWP (taxpayer identification number). Additionally, some MSMEs in Habi Village lacked knowladge and understanding about income tax, including how to properly register as taxpayers, resubmit notification letters, pay tax arrears before the due date, and calculate and pay taxes owed on their income.